Pengembangan Media Pembelajaran Interaktif Fisika Berbasis Macromedia Flash pada Materi Termodinamika untuk SMA: Development of Interactive Physics Learning Media Based on Macromedia Flash in Thermodynamic Material for SMA - Siti Barokah; Asrial Asrial; Maison Maison (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2019)
Physics is a science that is partly empirical and mathematical as well as abstract; therefore, it requires innovation to attract students' attention and motivation in learning. One of the suitable changes to be developed is in the form of interactive learning media based on Macromedia Flash. This study aims to develop an interactive learning media based on Macromedia Flash on thermodynamic materials and to find out the responses of teachers and students who use the media. This developmental research adopts the ADDIE development model. Material expert validated the product in two stages with the final percentage of 82.7% (very good/correct category). Media expert approved in two-stages with the final score of 91.2% (valid category). The small group test consisted of 8 students, and a large group test consisted of 18 students. The score of student response analysis in small groups 86.25% (very good categories), and large groups 83.40% (very good categories). The score response of the teacher 93.33% (very good category). The developed interactive learning media based on Macromedia Flash on thermodynamic material for class XI IPA Students of SMA is feasible to use.